Acquired bullous diseases of childhood: re-evaluation of diagnosis by indirect immunofluorescence examination on 1 M NaCl split skin and immunoblotting. - Kirtschig, G; Wojnarowska, F; Marsden, R; Edwards, S; Bhogal, B; Black, M (1994)
Acquired autoimmune bullous diseases of childhood are rare, and can be difficult to distinguish clinically. We have studied 12 children, with an initial diagnosis of bullous pemphigoid (BP) in eight patients, cicatricial pemphigoid (CP) in one, chronic bullous disease of childhood (CBDC) in one, and epidermolysis bullosa acquisita (EBA) in two. All patients had positive indirect immunofluorescence (IIF) of the BMZ with IgG. Using 1 M NaCl split skin, six patients showed epidermal binding of IgG, with additional IgA in three cases, and in five patients IgG antibodies bound a dermal protein. Immunoblotting studies revealed an antibody to type VII collagen (EBA antigen) in three patients who had a dermal pattern on IIF. Six sera reacted with an epidermal protein of 180 and/or 220 kDa, characteristic of BP and CP. One of the three IgA-positive sera detected 220- and 180-kDa epidermal proteins using anti-IgA antibody. Following these studies the diagnosis was changed in three of the children. The diagnosis of CBDC was changed to either BP or EBA because of the presence of circulating IgG autoantibodies. In two children with an initial diagnosis of BP the diagnosis was changed to EBA. We conclude that the clinical picture in bullous disorders of childhood shows considerable overlap, and is often misleading. Additional circulating IgA autoantibodies seem to be more common in BP than has been recognized previously. Indirect immunofluorescence investigation on 1 M NaCl split skin may be helpful in differentiating between BP and EBA, but does not replace immunoblotting studies. EBA is apparently more common in children than in adults. No difference was found between the children with BP and EBA with regard to the duration of disease. The long-term outlook is good, although the course may be protracted.